Kinerja kecerdasan buatan dalam mendeteksi fraktur tulang pada hasil radiografi : Sistematik Literatur Review - Stevany Nurifin (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2024)
Abstract Background: artificial intelligence (AI), is currently very widely used in various lines of human life, including in the health sector. Dalam ilmu radiologi peran AI sudah mulai dilibatkan dalam interpretasi pembacaan hasil pencitraan radiologi dengan tujuan agar penegakana diagnosis radiologis dapat berjalan lebih efisien. Purpose: To assess the performance of artificial intelligence in detecting human bone fractures on rediological imaging results. Method: A systematic literature review method using the PUBMED search application with a publication time span of the last 5 years using search queries (